EFFECTS OF HEALTH EDUCATION LEARNING MANAGEMENT APPLYING SELF-EFFICACY THEORY TOWARDS THE LEARNING ACHIEVEMENT ON THE TOPIC OF ACCIDENT PREVENTION AND FIRST AID FOR THE LOWER SECONDARY SCHOOL STUDENTS - Sirisombutyunyong, Chakrin; khamthoon, Puntasiri (Journal of Social Science and Cultural, 2025)
A quasi-experimental study aims to 1) Examine the effects of Health Education Learning Management, incorporating Self-efficacy Theory, on students’ learning achievement in accident prevention and first aid. 2) Compare the pre-experimental and post-experimental mean scores of learning achievement between the experimental and control groups. and 3) Assess students’ satisfaction with the learning approach health education learning management incorporating self-efficacy theory. The sample consisted of 60 Grade 7 students from Ongkharak Demonstration School who voluntarily participated in the study during the second semester of the 2024 academic year. Participants were divided into experimental or control groups, with 30 students in each. The intervention consisted of 6 lesson plans applying Self-efficacy Theory, with assessments including an achievement test, a self-efficacy assessment, and a satisfaction questionnaire. Data were analyzed using mean, standard deviation, and t-tests to examine differences. The findings revealed that after participating in Health Education Learning Management incorporating Self-efficacy Theory: 1) The experimental group demonstrated significantly higher mean scores in knowledge, attitudes, practice, and self-efficacy after the intervention at the .05 level; 2) The post-experimental mean scores of learning achievement and self-efficacy significantly differed between the experimental and control groups at the .05 level; and 3) The experimental group showed the highest level of overall satisfaction with participating in health education learning management incorporating self-efficacy theory.